Direct calculation method of roll damping based on three-dimensional CFD approach - 周耀华 马宁 石珣 章程 (Journal of hydrodynamics. Series B, 2015)
The effect of roll damping on the prediction of a ship＇s motion is significant. A method based on the 3-D CFD approach for calculating the roll damping of a ship is proposed in this paper. The free decay experiments of 4 different types of ships at zero velocity are carried out. The roll damping coefficients are calculated and compared with the experiment results, with a good agreement. It is shown that the method adopted in this paper could be used to simulate the free rolling of a ship in the calm water at zero velocity very well and with good, stable accuracy for the prediction of the roll damping, and also with good applicability. This method may be further developed for the prediction of a full scale ship in the future.